Parenting Initiatives in Uganda Learning from UZAZI AVSI Parenting Model and Related Initiatives - Walakira, Eddy J.; Matovu, Fred; Kyamulabi, Agnes; Biribonwa Agaba, Alfred; Nyeko, John Paul; Luwangula, Ronald (Fountain Publishers, 2021)
This book provides a national context and state of parenting in Uganda. It introduces the concept of parenting and helps the reader to gain an understanding of the attributes and dimensions that make parenting either successful on one hand or ineffective on the other. The book further sheds light on the evolving role of parents in the Ugandan context, identifies selected parenting interventions and in particular, pays greater attention to the UZAZI AVSI Parenting Model. UZAZI is positive parenting emphasizing authoritative nurturing of children. The presentation of the UZAZI AVSI Parenting Model gives the reader an opportunity to understand the effectiveness of the model based on its evaluation using rigorous scientific methods. The book concludes by making recommendations to improve research, policy and programming in the field of parenting within the context of families and children.
Keywords: Parenting Initiatives; Learning; UZAZI AVSI Parenting Model